Scientific Discourse about Energy Geopolitics: Changing Paradigms or Simply Adapting to New Times? - Costa, C. M.; Santos, A. (Changing the Paradigm of Energy Geopolitics: Security, Resources and Pathways in Light of Global Challenges, 2023)
Energy became a hot topic in international politics, raising several issues based on energy security concerns and the need for the energy transition to respond to a climate change demand. This chapter will analyze how the scientific discourse evolved in the past two decades and if the research topics reflect the context of climate change and energy transition. Simultaneously, we identify the most relevant scientific journals, the centres of research producing scientific discourse on this topic and the issues receiving increased attention from researchers. This research aims to answer our primary questions: has scientific discourse about energy geopolitics shifted in the source of its production or the topics considered the most significant? Is scientific discourse corresponding to the changes in political discourse about energy and energy geopolitics? We use the Scopus database as the resource for the scientific discourse and analyze the past two decades, focusing on the discourse production combining the analysis of scientific discourse with bibliometric data. The gathered data suggest newcomers in the list of leading producers of scientific discourse, a different geographic distribution of the producers and new trends on the researched topics, corresponding with the tendencies of political discussion about these issues.